EUTHANASIA SEBAGAI KONSEKUENSI KEBUTUHAN SAINS DAN TEKNOLOGI (Suatu Kajian Hukum Islam) - Arifin Rada (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Science and technology are part of human life that was born as a consequence of the development of science. One of science development which helped and directly related to human health and life, while life and death of human beings is something that has a high position in any moral values, so every treat against him would raises questions in terms of morale. This is the base for development of genetic engineering or biotechnology and bioethics as a field of science that is now considered a separate discipline in the field of medicine.Keywords: euthanasia, science, technology, Islamic law